Analisis Tingkat Kepuasan Peternak pada Sistem Kemitraan Ayam Broiler PT. Evaria Farm Di Kabupaten Bulukumba - Mita Dwijayanti; Muh. Ridwan; St. Rohani (Faculty of Agriculture, Musamus University, 2021)
Broiler chicken is one of the poultry commodities that has a very fast growth rate and high productivity, especially in producing chicken meat. In the broiler chicken partnership business, large companies provide inputs such as DOC, feed and medicines. The farmer provides a cage and equipment as well as labor for raising the chickens until harvest. This study aims to determine the level of farmer satisfaction in the broiler partnership system at PT. Evaria Farm. The research location was in Bulukumba Regency, South Sulawesi Province, which was carried out from December 2020 to January 2021. The type of research used was descriptive quantitative. The sample in this study were 28 partner breeders. The data were collected through interviews with the help of a questionnaire. The data analysis used in this research is the Imfortance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). The results showed an average level of performance analysis (IPA) was 4.30 and an interest rating of 4.98 with an average level of suitability of 86.35 and a Customer Satisfaction Index (CSI) of 86.04, meaning that the level of farmer satisfaction in the partnership system as a whole are on the criteria very satisfied